Caffeic Acid Phenethyl Ester Inhibits Epithelial-Mesenchymal Transition of Human Pancreatic Cancer Cells. (4th April 2013) - Chen, Ming-Jen; Shih, Shou-Chuan; Wang, Horng-Yuan; Lin, Ching-Chung; Liu, Chia-Yuan; Wang, Tsang-En; Chu, Cheng-Hsin; Chen, Yu-Jen
Abstract : Background . This study aimed to investigate the effect of propolis component caffeic acid phenethyl ester (CAPE) on epithelial-mesenchymal transition (EMT) of human pancreatic cancer cells and the molecular mechanisms underlying these effects. Methods . The transforming growth factor β (TGF-β -) induced EMT in human pancreatic PANC-1 cancer cells was characterized by observation of morphology and the expression of E-cadherin and vimentin by western blotting. The migration potential was estimated with wound closure assay. The expression of transcriptional factors was measured by quantitative RT-PCR and immunocytochemistry staining. The orthotopic pancreatic cancer xenograft model was used for in vivo assessment. Results . The overexpression of vimentin was attenuated by CAPE, and the alteration in morphology from polygonal to spindle shape was partially reversed by CAPE. Furthermore, CAPE delayed the TGF-β -stimulated migration potential. CAPE treatment did not reduce the expression levels of Smad 2/3, Snail 1, and Zeb 1 but inhibited the expression of transcriptional factor Twist 2. By using an orthotopic pancreatic cancer model, CAPE suppressed the expression of Twist 2 and growth of PANC-1 xenografts without significant toxicity. Conclusion . CAPE could inhibit the orthotopic growth and EMT of pancreatic cancer PANC-1 cells accompanied by downregulation of vimentin and Twist 2 expression.